Comparison of a Micromethod for Performance of the Serum Bactericidal Test with the Standard Tube Dilution Method - Prober, Charles G. (1979)
A micromethod for performance of the serum bactericidal test is described, and the results obtained with this method are compared with those obtained with the standard tube dilution macromethod. An agreement within ± 1 dilution was achieved in 23 of 25 (92%) determinations of the serum bactericidal titer. The micromethod used approximately one-third of the amount of pooled normal human serum and of the technician's time required for performance of the macromethod. The micromethod offers an accurate and economical alternative to the macromethod for the performance of the serum bactericidal test and is particularly useful with infants and children since it minimizes blood loss.